Bridging the rural divide in STEM Education through culture, design thinking & gamification in Malaysia - Fitri Suraya, Mohamad; Minoi, Jacey Lynn (Arts and Humanities Research Council (AHRC) UK, 2018)
Research funded by AHRC and the Newton Fund is creatively transforming approaches to education for school children in rural areas of Malaysia through game design and computational thinking. Malaysian school children in under-resourced areas have increased their engagement with STEM subjects and developed stronger soft skills through these practices.